Alterations in bone fracture healing associated with TNFRSF signaling pathways - Dong, Yanzhao; Zhou, Haiying; Alhaskawi, Ahmad; Wang, Zewei; Lai, Jingtian; Abdullah Ezzi, Sohaib Hasan; Kota, Vishnu Goutham; Abdulla Hasan Abdulla, Mohamed Hasan; Sun, Zhenyu; Lu, Hui (Frontiers in Pharmacology, 2022)
Bone fracture healing is a complex process involving various signaling pathways. It remains an unsolved issue the fast and optimal management of complex or multiple fractures in the field of orthopedics and rehabilitation. Bone fracture healing is largely a four-stage process, including initial hematoma formation, intramembrane ossification, chondrogenesis, and endochondral ossification followed by further bone remodeling. Many studies have reported the involvement of immune cells and cytokines in fracture healing. On the other hand, the Tumor Necrosis Factor (TNF) family and TNF receptor superfamily (TNFRSF) play a pivotal role in many physiological processes. The functions of the TNF family and TNFRSF in immune processes, tissue homeostasis, and cell differentiation have been extensively studied by many groups, and treatments targeting specific TNFRSF members are in progress. In terms of bone fracture management, it has been discovered that several members of TNFRSF have very distinct functions in different stages of fracture healing, including TNFR1, TNFR2, and receptor activator of nuclear factor kappa-B (RANK) pathways. More specifically, TNFR1 is associated with osteoclastogenesis and TNFR2 is associated with osteogenic differentiation, while RANK is in association with bone remodeling. In this review, we will discuss and summarize the involvement of members of TNFRSF including TNFR1, TNFR2, and Receptor activator of nuclear factor kappa-B (RANK) pathways in different stages of fracture healing and bone remodeling and the current treatment trend involving TNFRSF agonists and antagonists.